A geography of reconciliation : An effective and lawful framework for achieving clarity of First Nations territorial jurisdiction in British Columbia - Turner, R.G. Christopher (Author); Fondahl, Gail (Thesis advisor); Murphy, Michael (Thesis advisor); Hoffman, Ross (Committee member); Krehbiel, Richard (Committee member); Nolin, Catherine (Committee member); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2018)
What is the best way to achieve and sustain clarity of First Nations territorial jurisdiction in British Columbia (BC)? The question is critical to addressing the legal imperative of Indigenous-Crown reconciliation; that is, balancing the rights of Indigenous peoples with the interests of society as a whole through negotiation. Reconciliation requires dialog, and effective dialog is almost impossible amidst conflict concerning which Indigenous polities have legal authority to negotiate concerning specific territories. This dissertation argues that hybrid law – involving the harmonization of state and Indigenous legal systems – should be the basis of common understanding and legitimacy for determining which Indigenous polities have legal authority to negotiate concerning areas subject to “overlapping claims”. Drawing upon the experiences of BC, New Zealand, and Australia, the study concludes that First Nations and the Crown in BC should work collaboratively to empower an independent Indigenous Territories Tribunal to oversee a program of regional inquiries across the province. Regional inquiries should involve: a) research, b) community hearings that empower Indigenous people to articulate their history and legal systems, c) assessments of the character and strength of claims, d) recommendations, and e) the development of Indigenous Jurisdiction Agreements that express complex Indigenous territorialities, hybrid law, and the Indigenous polities that have the legal authority to negotiate with the Crown concerning specific territories. Clarity of Indigenous territorial jurisdiction is a critical aspect of addressing the legal imperative of Indigenous-Crown reconciliation. This dissertation proposes a framework for achieving a geography of reconciliation: that is, an exhaustive map of BC that clearly communicates which First Nation polities have legal authority to negotiate where. geography of reconciliation First Nations territorial jurisdiction Indigenous legal system